Функциональное тестирование программноаппаратных комплексов - Мостовая, К. Л.; Денисов. Е. А. (ХНУРЭ, 2009)
The given work is devoted to the functional testing approach of modern HW/SW systems in order to confirm that product meets the initial functional expectations. The work presents the approach of testing HW and SW components of complex digital systems.